Tipping water balance and the Pt loading effect in polymer electrolyte fuel cells: a model-based analysis. Issue 6 (10th April 2018) - Muzaffar, Tasleem; Kadyk, Thomas; Eikerling, Michael
Abstract : Tipping water balance drastically affecting the performance of electrode layers in polymer electrolyte fuel cells with low Pt loading. Abstract : The commercial deployment of polymer electrolyte fuel cells (PEFCs) hinges on breakthroughs in design and integration of highly performing and durable catalyst layers with markedly reduced platinum loading. Experimental studies have shown an unexpected increase in voltage losses upon a drastic reduction in the Pt content. In an effort to unravel this peculiar behavior, an existing physical model of catalyst layers in PEFCs is employed to analyze a wide range of fuel cell performance data from the literature. The analysis reveals correlated trends in key fuel cell parameters. These findings can be explained in view of the tipping water balance that affects the interplay of transport and reaction in catalyst layer and gas diffusion media. This represents a compelling alternative to the widespread ionomer-film hypothesis that links observed power losses at low Pt loading to a mesoscopic oxygen transport resistance. The presented theoretical analysis warrants the definition of a correlation exponent that should find use in assessing the merit of different approaches in catalyst layer fabrication.